1970
DOI: 10.20952/revtee.v0i0.2194
|View full text |Cite
|
Sign up to set email alerts
|

O Controle do Espaço, do Tempo e das Atividades no Internato da Escola Agrotécnica Federal de São Cristóvão-SE

Abstract: Este artigo é uma abordagem histórica do exercício do “poder disciplinar” no internato da Escola Agrotécnica Federal de São Cristóvão-SE (EAFSC-SE) e faz parte de um estudo mais amplo sobre a “pedagogia de internar” na referida instituição, no período de 1934 a 1967. São evidenciadas e analisadas as técnicas disciplinares de controle do espaço, do tempo e das atividades diárias dos internos. Os espaços do internato eram controlados pelas técnicas de distribuição dos internos em lugares fixos ou específicos, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As such, collective rooms go back, while past sign fragment [26], to dormitories for groups of people from the first lodgings for religious pilgrims in the Middle Ages [33], or they go back to collective rooms of colleges and boarding schools [105,106]. In these examples from the past, strict discipline and rigid rules underpinned the learning of mutual respect when adhering to egalitarian codes of conduct i.e., they established the social (de)hierarchization for inmates [105]. Rizzini and Rizzini [106] have shown that children of former Brazilian black slaves confined to orphanage rooms have developed a collective consciousness of their ethnic and social insertion in republican Brazil.…”
Section: Research Objectmentioning
confidence: 99%
“…As such, collective rooms go back, while past sign fragment [26], to dormitories for groups of people from the first lodgings for religious pilgrims in the Middle Ages [33], or they go back to collective rooms of colleges and boarding schools [105,106]. In these examples from the past, strict discipline and rigid rules underpinned the learning of mutual respect when adhering to egalitarian codes of conduct i.e., they established the social (de)hierarchization for inmates [105]. Rizzini and Rizzini [106] have shown that children of former Brazilian black slaves confined to orphanage rooms have developed a collective consciousness of their ethnic and social insertion in republican Brazil.…”
Section: Research Objectmentioning
confidence: 99%